Influence of Skin Phototype on the Level of Pain Perceived by Patients Receiving Enoxaparin: A Cross-Sectional Study - Candelaria de la Merced Díaz-González; Josefa María Ramal-López; Juan José González-Henríquez; Milagros de la Rosa-Hormiga (MDPI AG, 2022)
Low Molecular Weight Heparin (LMWH) is commonly used as an antithrombotic in patients with reduced mobility. Its administration is performed by invasive technique (injections) that can cause pain: (1) Background: Pain and bruising are the most common side effects in patients treated with LMWH, but the skin phototype (PT) has never been included; (2) Methods: A cross-sectional descriptive study, developed in the Hospital Unit of Orthopedic and Trauma Surgery over one year. To classify all participants in the sample considering their skin PT and the different pain levels "during" and "after" the administration of enoxaparin. The STROBE checklist was used to evaluate the study. Data analyses were carried out: descriptive statistical analysis and analysis of Variance ANOVA of a non-parametric factor; (3) Results: The sample was 202 participants. The most frequent skin PTs were PT II 43.6% and PT III 33.2%. Mean pain after injection (1.96) was greater than pain during injection (1.4). Better natural protection against sunlight (high PT) would indicate greater post-injection pain; (4) Conclusions: Participants with a medium-high phototype (≥III) perceive a greater pain sensation than participants with a low phototype (≤II) after the administration of enoxaparin.